An Examination of The Relationship Between Corporate Social Responsibility, Corporate Image and Customer Loyalty: The Mediating Role of Customer Attitude - Rachmat Hidayat; Endang Saefuddin Mubarok; Rukun Santoso; Wiwin (Yayasan Ilomata, 2021)
This study aimed at understanding the effects of corporate social responsibility, corporate image, customer attitude, and customer loyalty. The method used for this study was causality and non-probability sampling and purposive sampling were used as the data collection methods. The data source in this study was primary data collected using questionnaire instruments. The number of samples of the study was 100 respondents. The data analysis model in this study used path diagrams in the form of regression equations. The results of the statistical study showed that: (1) Corporate social responsibility and customer immunity both partially and simultaneously had a positive effect on customer attitude, (2) Corporate social responsibility and corporate image, both partially and simultaneously, had a positive effect on customer loyalty. (3) Corporate social responsibility, customer image, and customer attitude simultaneously had a significant effect on customer loyalty. Partially, only corporate social responsibility and customer image had a significant effect on customer loyalty, while customer attitude had no significant effect. (4) The customer attitude variable was able to mediate the effects of corporate social responsibility and customer image on customer loyalty.